Bacterial Communities Predominant in the Degradation of 13C-Labeled Pyrene in Red Soil. Issue 7 (17th November 2017) - Guo, Guang; Tian, Fang; Ding, Keqiang; Wang, Lihong; Liu, Tingfeng; Yang, Feng
ABSTRACT: The bacterial community composition using a consortium (CON) with or without methyl-β-cyclodextrin (MCD), used to bioremediate the pyrene-contaminated soil was evaluated through stable-isotope probing (SIP). Microcosms were artificially contaminated with 13 C pyrene at 15 ppm, and bacterial community composition was determined over a 14-day period. After 14 days, only 29.1% of pyrene was degraded in control, while 90.6% of pyrene was degraded by the bacterial community with MCD, showing the best bioremediation rate of all treatments. After 14 days, PAH degraders became dominated by Proteobacteria. Sphingomonas and Pseudomonas were the predominant genera in all treatments, and Pseudomonas was the main degrader from the bacterial community. The bacterial community was little affected by MCD. The results indicated that the combination of the bacterial community with MCD can be used to bioremediate PAHs polluted soil.